Marianismo and the Catholic Autobiographer: A Comparative Analysis - Lee, Nina (AUC Knowledge Fountain, 2022)
As a version of femininity that derives from the figure of the Mother Mary, marianismo emphasizes the traditional roles of self-sacrifice, motherhood, spirituality, and nurturance. While marianismo is most often associated with Latin America, it can be traced back to Catholicism’s origins in Europe. Early and medieval Catholic theologians, such as Saint Augustine of Hippo and Peter Abelard, demonstrate marianista beliefs within their autobiographical writings. As autobiography is purported to be the most intimate window into both the personal and larger social situations of a given time and place, the autobiographies of such Catholic male theologians provide insight into the source as well as perpetuation of marianista ideology. Through analyzing Augustine and Abelard’s relationships with and descriptions of women, this thesis investigates the gender roles of women as they align with those of marianismo. Being distinctly Catholic autobiographers as well as members of the clergy, the respective works of these theologians underline the direct connections between marianismo and the institution of the Catholic Church, demonstrating how women are expected to emulate the Virgin Mary through their chastity, motherhood, and spirituality.